The limits on limited liability: a comparative analysis of piercing the corporate veil in Swedish and South African law - Richard, Chelsea (Department of Commercial Law, 2024)
The doctrine of piercing the corporate veil assumes a controversial role in both Sweden and South Africa. When making affirmative veil-piercing decisions, both countries' courts are faced with the choice of whether to defend the principle of limited liability, as an inherently respected component of company law, or to neglect a company's separate legal personality and reveal abusive situations. Over the last few decades, the precise approach to be embraced when making such a decision has followed a trend of inconsistency in both jurisdictions. The purpose of this paper is therefore to examine the common law and statutory law in both South Africa and Sweden to ascertain the current position regarding veil-piercing and to establish whether the law, as it presently stands, affords sufficient guidance for courts to pierce the veil. This will be enhanced by the fact that the paper encompasses a comparison between a common law and civil law jurisdiction. Ironically, it is the former, South Africa, which has elected to endorse the doctrine by codifying it in the 2008 Companies Act, but the latter, Sweden, has tended to safeguard the principle of limited liability by refusing to codify it.